Clinical relevance of frozen diagnosis of ductal margins in surgery of bile duct cancer. (21st January 2014) - Furukawa, Toru; Higuchi, Ryota; Yamamoto, Masakazu
Abstract It is anticipated that free surgical margin is crucial for curative resection of bile duct cancer. However, the clinical relevance of the ductal margin is somewhat controversial. A role of frozen section diagnosis used for evaluation of the ductal margin during surgery is also ambiguous. We reviewed the current knowledge about frozen section diagnosis and the clinical relevance of the margin status in surgery of the bile duct cancer. Frozen section diagnosis of the ductal margin of bile duct cancer is necessary to ensure free margins; however, it is quite challenging even for experienced pathologists because the bile duct involved with bile duct cancer is often inflamed severely due to obstruction and/or insertion of a draining tube, which induces epithelial regeneration with atypia. Also accessory ducts/peribiliary glands and their conduits in ductal wall can mimic invasive ductal components, which requires careful examination to evaluate regenerative change, carcinoma in situ, or invasive carcinoma. Published studies assessing an association between the ductal margin state and prognosis in relatively large cohorts of patients undergoing surgery for bile duct cancer indicate that the ductal margin status is an independent prognostic factor; and the ductal margin with carcinoma in situ is comparable to free margin; however, the margin with invasive carcinoma is significantly adverse for patients' prognoses.